DEEPENING CONVICTIONS; LEADING FOR RELIGIOUS LITERACY BASED ON PESANTREN - Umar, Umar (Nurul Jadid University, 2023)
The flood of information due to the emergence of information technology makes it easier for someone to view and study any information obtained without meeting the author face to face. The impact of authenticity on whether the information obtained can be accounted for. The effort to answer this challenge is a person's literacy skills to avoid getting caught up in wholly inauthentic and irresponsible disinformation. Pesantren also carry out efforts to overcome the problem of floods of information and religious literacy as an educational institution concentrating on religious understanding compared to other scientific fields. Based on this, this research aims to understand the strategies of Islamic boarding school leaders in building religious literacy skills. This research was conducted using a qualitative approach with a case study type. The research results show that leaders' strategies for building religious literacy skills are carried out through establishing religious literacy policies in the vision and mission and developing religious literacy based on local characteristics. Religious literacy based on local characteristics is implemented by reading the al-Qur’an and kitab kuning daily, using various learning methods to improve reading skills, collaborating with other Islamic boarding schools, having a well-equipped library, regular library visits, and promotions. An inclusive oral culture that encourages open and respectful discussion.